2017
DOI: 10.1093/schbul/sbx093
|View full text |Cite
|
Sign up to set email alerts
|

N-acetylcysteine in a Double-Blind Randomized Placebo-Controlled Trial: Toward Biomarker-Guided Treatment in Early Psychosis

Abstract: Biomarker-guided treatments are needed in psychiatry, and previous data suggest oxidative stress may be a target in schizophrenia. A previous add-on trial with the antioxidant N-acetylcysteine (NAC) led to negative symptom reductions in chronic patients. We aim to study NAC’s impact on symptoms and neurocognition in early psychosis (EP) and to explore whether glutathione (GSH)/redox markers could represent valid biomarkers to guide treatment. In a double-blind, randomized, placebo-controlled trial in 63 EP pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
135
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(142 citation statements)
references
References 55 publications
6
135
1
Order By: Relevance
“…Furthermore, feasibility data indicated high tolerability, as retention was consistently high and adherence was >80%. Both of the trials of taurine (O'Donnell et al, 2016) and NAC (Conus et al, 2017) also reported that there were no adverse side-effects from either of these amino acids in FEP. Similarly, adjunctive treatment with antioxidant vitamins (C and E) did not result in any adverse events or side-effects (Dakhale et al, 2005;Eranti et al, 1998).…”
Section: Side-effects and Adverse Eventsmentioning
confidence: 97%
“…Furthermore, feasibility data indicated high tolerability, as retention was consistently high and adherence was >80%. Both of the trials of taurine (O'Donnell et al, 2016) and NAC (Conus et al, 2017) also reported that there were no adverse side-effects from either of these amino acids in FEP. Similarly, adjunctive treatment with antioxidant vitamins (C and E) did not result in any adverse events or side-effects (Dakhale et al, 2005;Eranti et al, 1998).…”
Section: Side-effects and Adverse Eventsmentioning
confidence: 97%
“…Furthermore, one RCT reported efficacy not only with negative and cognitive symptoms but also with positive symptoms in chronic schizophrenia . Moreover, a recent RCT demonstrated continuous effects of adjunctive NAC approach in long‐term treatment and effects in early psychosis . A recent meta‐analysis from 6 RCT showed that adjunctive NAC appears to have efficacy for schizophrenia …”
Section: Treatment Based On Glutamate Hypothesismentioning
confidence: 99%
“…Preliminary results have demonstrated that NAC, a GSH precursor, may be beneficial in psychotic disorders [69]. NAC has been shown to be efficacious in reducing the symptom burden [70], especially negative [71] and cognitive symptoms [72], and has the potential to alleviate treatment resistance in schizophrenia [73].…”
Section: Limitationsmentioning
confidence: 99%
“…Our results suggest that treatments such as NAC may be efficacious particularly in patients who demonstrate an early poor response to antipsychotic medication, as they are likely to have a lower ability to synthesize GSH in response to glutamatergic excess. While MRS indices are indirect measures of tissue metabolite concentrations [74], given the evidence that oral NAC administration in patients with schizophrenia increases GSH content in the ACC [69], we consider MRS as a viable tool for translational investigations into the redox abnormalities of schizophrenia. More speculatively, we suggest that the association of ACC GSH levels at baseline and eventual clozapine-eligibility would be worth investigating in the future, given the lack of objective predictors of clozapine requirement in schizophrenia.…”
Section: Limitationsmentioning
confidence: 99%